DEVELOPMENT OF A VIRTUAL REALITY-BASED FIRE SAFETY TRAINING SYSTEM FOR APARTMENT RESIDENTS - Ussenov, Bekzat; Temen, Arnur; Srymbetov, Zhalgas; Yeshmukhametov, Azamat; Akhmetov, Tolegen (Scientific Journal of Astana IT University, 2025)
Fire safety training is crucial for preventing injuries and property damage during emergencies. Traditional training methods, such as physical drills and lectures, suffer from low engagement, high costs, and limited realism. Virtual reality technology offers an innovative approach to improve fire safety education by providing an immersive and interactive training environment. This paper presents the development of a virtual reality-based fire safety training system for apartment residents, designed for a head-mounted display. The system incorporates realistic fire simulations and mechanics for interactive fire extinguishing. Our study explores both qualitative and quantitative measurements of a virtual reality (VR) training model, comparing it with alternative video-based training for fire safety. The experiment involved 20 participants who underwent training using either our VR system or video instructions, divided into two groups. After the VR training, participants completed a presence questionnaire and a knowledge test. Objective metrics included overall escape time and completion rate. Subjective data were collected through semi-structured interviews conducted after the experiments. Results indicate a significant difference in presence scores and higher knowledge scores for the VR group (VR: M = 10.9, SD = 2.37; Video: M = 7.3, SD = 1.33). These findings suggest that immersive VR training enhances procedural learning and situational awareness more effectively than passive video instruction. The study contributes to the field of VR in safety education by offering empirical evidence of its advantages and highlighting gaps in user engagement and realism in conventional methods. Limitations include the small sample size and short-term retention measurement. Future work will explore larger-scale evaluations and the integration of AR for blended learning experiences.